Characterization of Stroke Patients in an Intensive Care Unit - Marianela Planes Fajardo; Georgia Díaz-Perera Fernández; Maylín Isabel Alonso Martínez; Aurora Calzada Fajardo (Universidad de las Ciencias Médicas de Cienfuegos, 2021)
Background: cerebrovascular diseases represent a potentially serious panorama, with avoidable consequences and whose prognosis depends on the speed and effectiveness of the actions. Stroke is the main neurological cause of death and the third most common cause of death in the world. Objective: to characterize the clinical-epidemiological variables of stroke patients in the Havana Institute of Neurology and Neurosurgery´s Intensive Care Unit. Method: a retrospective research was carried out that included 30 patients admitted with a diagnosis of stroke, in the Neurology and Neurosurgery Institute´s intensive care unit from January to December 2020. Demographic and clinical variables were considered, as well as the status at discharge and the hospital stay. Descriptive statistics were performed for continuous variables: means and standard deviation, and for qualitative variables: absolute and relative frequencies and the Chi Square test were performed to determine the possible association between variables. Results: the mean age of the patients was 59.4 years. 20 % were obese, a history of smoking was present in 73.3 % and type 2 diabetes mellitus in 70 %. Hemorrhagic stroke occurred in 63.3 % of the cases. 6 patients died for 20 % who had as risk factors, diabetes in 100 %, age over 60 years old in 83.3 % and obesity in 50 %. The average hospital stay was 13.9 days and was higher in patients who consumed alcohol and those who had hemorrhagic stroke. Conclusions: the risk factors with the highest frequency were: smoking, type 2 diabetes mellitus and age over 60 years old.